2006
DOI: 10.1111/j.1574-6968.2006.00396.x
|View full text |Cite
|
Sign up to set email alerts
|

Human epithelial-specific response to pathogenicCampylobacter jejuni

Abstract: The gastrointestinal epithelia of mammals are tolerant of their resident gut microbiota but are usually highly responsive to entero-pathogens; the host-specific responses have not been well characterized. To this end, the transcriptional responses of cultured human (Caco-2) and murine (CT-26) colonic epithelial cells were compared after exposure with the microfloral bacterium Lactobacillus reuteri or the human gastrointestinal pathogen Campylobacter jejuni. When in bacterial broth, both species elicit a strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
(36 reference statements)
2
8
1
Order By: Relevance
“…A central role for NF-κB is also supported by data using the monocytic cell line THP-1 [23]. Studies in which Caco-2 cells were incubated with live bacteria resulted in expression of many genes similar to those reported here, including chemokines, but additionally, the NF-κB inhibitor NFKBIZ [24]. This difference may reflect the ability of live bacteria to invade cells and/or elaborate a CLDT with DNase activity [6].…”
Section: Discussionsupporting
confidence: 58%
“…A central role for NF-κB is also supported by data using the monocytic cell line THP-1 [23]. Studies in which Caco-2 cells were incubated with live bacteria resulted in expression of many genes similar to those reported here, including chemokines, but additionally, the NF-κB inhibitor NFKBIZ [24]. This difference may reflect the ability of live bacteria to invade cells and/or elaborate a CLDT with DNase activity [6].…”
Section: Discussionsupporting
confidence: 58%
“…In fact, we have observed the bacteria confined to blood vessels in the labyrinth rather than in the placental tissues, suggesting a different invasion mechanism in vivo . Similarly, it is known that differences exist in the response of human and murine epithelial cells to other Campylobacter species, as evidenced by differences in the expression of genes involved in growth, transcription and steroid biosynthesis in human colonic epithelia vs. unresponsive murine colonic cells (Rinella et al, 2006). Others have also reported that C. jejuni , which normally does not bind to Chinese hamster ovary cells, binds avidly when these cells are transfected with the human alpha1,2-fucosyltransferase gene, thus further demonstrating the specificity of Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Campylobacter, like Salmonella, Yersinia, Shigella and Listeria, is an organism capable of translocation, as demonstrated by the current and previous monolayer studies and clinical features that include septicemia, GuillainBarre syndrome and meningitis [16,33,34,41] . Previous studies have left unclear whether the main route is transcellular or paracellular.…”
Section: A B C D E Fmentioning
confidence: 99%
“…This increase in bradykinin-induced chloride secretion may therefore occur by prostaglandin-independent mechanisms. Direct epithelial action, via cAMP, cGMP, calcium mobilization, or induction of galanin or inducible nitric oxide are alternative mechanisms that are activated directly by bacterial enterotoxins or via signaling mechanisms that include NF-κB, which we and others have shown are upregulated by components of C. jejuni [24][25][26][27][40][41][42][43] . Destruction of the monolayer by strains that did invade epithelial cells and stimulate prostaglandin synthesis makes it difficult to evaluate whether enhanced prostaglandin synthesis by epithelial cells contributed to secretory diarrhea in these cases.…”
Section: A B C D E Fmentioning
confidence: 99%